Two Novel Mutations in the JAG1 Gene in Pediatric Patients with Alagille Syndrome: The First Case Series in Czech Republic - Prochazková, Dagmar; Borská, Romana; Fajkusová, Lenka; Konečná, Petra; Hloušková, Eliška; Pavlovský, Zdeněk; Slabý, Ondřej; Pospíšilová, Šárka (Diagnostics (Basel, Switzerland), 2021)
BACKGROUND: Alagille syndrome (ALGS) is a highly variable multisystem disorder inherited in an autosomal dominant pattern with incomplete penetration. The disorder is caused by mutations in the JAG1 gene, only rarely in the NOTCH2 gene, which gives rise to malformations in multiple organs. Bile duct paucity is the main characteristic feature of the disease. METHODS: Molecular-genetic examination of genes JAG1 and NOTCH2 in four probands of Czech origin who complied with the diagnostic criteria of ALGS was performed using targeted next-generation sequencing of genes JAG1 and NOTCH2. Segregation of variants in a family was assessed by Sanger sequencing of parental DNA. RESULTS: Mutations in the JAG1 gene were confirmed in all four probands. We identified two novel mutations: c.3189dupG and c.1913delG. Only in one case, the identified JAG1 mutation was de novo. None of the parents carrying JAG1 pathogenic mutation was diagnosed with ALGS. CONCLUSION: Diagnosis of the ALGS is complicated due to the absence of clear genotype-phenotype correlations and the extreme phenotypic variability in the patients even within the same family. This fact is of particular importance in connection to genetic counselling and prenatal genetic testing.
Keywords: Alagille syndrome; cholestasis; pediatric patients; JAG1 gene